Assessing the Career Readiness of Students in Bengkulu and Understanding How the Secondary Cultural Values of the Serawai Tribe Provide a Framework for Career Guidance in Vocational Schools - Juwanto, Juwanto; Nurihsan, Juntika; Rusmana, Nandang; Maya, Dian Mustika; Nalman, Annie Rachmawati (Universitas Negeri Padang, 2024)
This study explores the career readiness of vocational school students in Bengkulu and examines how secondary cultural values, particularly the Serawai tribe’s Sekundang Setungguan philosophy, can inform effective career guidance frameworks. Utilizing a quantitative descriptive methodology with a survey approach, data were collected from 347 students across grades X, XI, and XII through a Career Readiness Inventory distributed via Google Forms. The inventory's validity and reliability were tested using the Rasch model with Winstep software, resulting in 37 valid items out of 42. Findings indicate weak career readiness among students in key areas such as career exploration, decision-making, job information access, and occupational knowledge. Gender analysis reveals higher readiness levels among female students, while the Serawai ethnic group outperforms others in career preparedness. Factors influencing career planning include parental aspirations, limited guidance, and cultural diversity. The study underscores the importance of fostering career awareness early, incorporating cultural strengths into guidance programs. The Serawai values of cooperation, resilience, and mutual support provide a foundation for cultivating responsibility, empathy, and perseverance among students. These cultural frameworks can address career uncertainties and enhance readiness through collaborative efforts involving families, schools, and communities. By leveraging cultural values and fostering robust support systems, vocational students are better equipped to navigate challenges and seize opportunities, contributing to societal growth. The findings highlight the significance of culturally informed guidance to prepare students for the complexities of the modern workforce.